Frailty and nutritional assessments for predicting postoperative complications in older adults undergoing non-cardiac surgery - Chatmongkolchart, Sunisa; Saetang, Mantana; Kittisopaporn, Panalee; Kunapaisal, Thitikan; Yongsata, Dararat; Sukitpaneenit, Khwanrut (Frontiers in Medicine, 2025)
IntroductionFrailty and malnutrition are closely linked to adverse surgical outcomes. However, their combined influence on post-non-cardiac surgery complications in older patients remains unclear. We aimed to evaluate the predictive value of frailty, malnutrition, and their combined effect on postoperative complications in older patients undergoing intermediate- to high-risk non-cardiac surgery.MethodsThis study was a retrospective analysis of data from a prospectively collected cohort that included 637 patients aged ≥60 years. We assessed frailty using the Clinical Frailty Scale (CFS) and nutritional status using the Prognostic Nutritional Index (PNI). The primary outcome was the occurrence of postoperative complications (Clavien-Dindo classification ≥2). We used logistic regression and receiver-operating characteristic (ROC) analyses to determine the predictive accuracy of CFS, PNI, and CFS + PNI.ResultsWe identified frailty (CFS ≥ 5) in 38.5% of patients, with 29.8% being malnourished (PNI < 45). Multivariate analysis revealed that frailty independently predicted postoperative complications (odds ratio [OR]: 2.09, 95% confidence interval [CI]: 1.09–4.00; p = 0.026). Severe malnutrition (PNI < 40) exhibited a strong association with complications in univariate analysis (OR: 5.88, 95%CI: 3.13–11.08; p < 0.001) but not in multivariate analysis. The combined CFS + PNI model showed enhanced discriminative ability (area under the curve [AUC]: 0.694, 95%CI: 0.647–0.740) compared with CFS (AUC: 0.619, 95%CI: 0.575–0.662) or PNI (AUC: 0.665, 95%CI: 0.618–0.712) alone.ConclusionFrailty is a strong independent predictor of postoperative complications in older patients undergoing non-cardiac surgery. Although severe malnutrition correlates with increased risk, its effect may be partially mediated by frailty. The integration of frailty and nutritional assessments enhances postoperative complication prediction, underscoring comprehensive geriatric evaluation value in preoperative risk stratification.